Crystal structure of the B7-1/CTLA-4 complex that inhibits human immune responses. - Stamper, C; Zhang, Y; Tobin, J; Erbe, D; Ikemizu, S; Davis, S; Stahl, M; Seehra, J; Somers, W; Mosyak, L (2001)
Optimal immune responses require both an antigen-specific and a co-stimulatory signal. The shared ligands B7-1 and B7-2 on antigen-presenting cells deliver the co-stimulatory signal through CD28 and CTLA-4 on T cells. Signalling through CD28 augments the T-cell response, whereas CTLA-4 signalling attenuates it. Numerous animal studies and recent clinical trials indicate that manipulating these interactions holds considerable promise for immunotherapy. With the consequences of these signals well established, and details of the downstream signalling events emerging, understanding the molecular nature of these extracellular interactions becomes crucial. Here we report the crystal structure of the human CTLA-4/B7-1 co-stimulatory complex at 3.0 A resolution. In contrast to other interacting cell-surface molecules, the relatively small CTLA-4/B7-1 binding interface exhibits an unusually high degree of shape complementarity. CTLA-4 forms homodimers through a newly defined interface of highly conserved residues. In the crystal lattice, CTLA-4 and B7-1 pack in a strikingly periodic arrangement in which bivalent CTLA-4 homodimers bridge bivalent B7-1 homodimers. This zipper-like oligomerization provides the structural basis for forming unusually stable signalling complexes at the T-cell surface, underscoring the importance of potent inhibitory signalling in human immune responses.